2016
DOI: 10.1155/2016/6891482
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Programmed Death-1 and Programmed Death Ligand-1 Negatively Regulates Immune Response against Cervical Cancer Cells

Abstract: The present study is to measure the expression of programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1), as well as its clinical significance in cervical cancer patients. Our results showed that different T cell subsets in patients with cervical cancer had high expression of PD-1, and DCs had high expression of PD-L1. High expression of PD-1 on Treg cells in cervical cancer patients facilitated the production of TGF-β and IL-10 but inhibited the production of IFN-γ. Cervical cancer elevated the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
1
40
0
1
Order By: Relevance
“…Finally, there is one more important source of PD-L1 among adaptive immune cells represented by regulatory T cells (Treg); a correlation between PD-L1 expression and FoxP3+Treg was reported by Ma et al [75]. Moreover, CD4CD25 Tregs are able to upregulate PD-1 expression in patients with CIN/ cervical carcinoma [36], which, however, does not result in Treg exhaustion, but, conversely, favors upregulation of their immunosuppressive activity. Lastly, it has been reported that regional lymph nodes from stage IB1 cervical cancer patients, along with elevated PD-1, have increased expression of FoxP3 Treg-marker, which may shed light on the establishment of pre-metastatic niches [71], as well as on systemic expansion of suppressive mechanisms Tregs are engaged in.…”
Section: Regulatory T and B Cells And Immune Checkpoint Molecules In mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, there is one more important source of PD-L1 among adaptive immune cells represented by regulatory T cells (Treg); a correlation between PD-L1 expression and FoxP3+Treg was reported by Ma et al [75]. Moreover, CD4CD25 Tregs are able to upregulate PD-1 expression in patients with CIN/ cervical carcinoma [36], which, however, does not result in Treg exhaustion, but, conversely, favors upregulation of their immunosuppressive activity. Lastly, it has been reported that regional lymph nodes from stage IB1 cervical cancer patients, along with elevated PD-1, have increased expression of FoxP3 Treg-marker, which may shed light on the establishment of pre-metastatic niches [71], as well as on systemic expansion of suppressive mechanisms Tregs are engaged in.…”
Section: Regulatory T and B Cells And Immune Checkpoint Molecules In mentioning
confidence: 99%
“…Interestingly, according to Swangphon et al, cervical cancer patients exhibit altered ratio of M1/M2-polarized (CD64+/CD163+) monocytes not only at the local level, but in systemic circulation as well; notably, circulating M1/M2 ratio was shown to be correlated with the number of stroma-or peritumoral area-infiltrating M2-macrophages (CD163+), and with severity of the disease [35]. Similarly, cervical cancer patients displayed increased numbers of circulating dendritic cells (CD11b+) expressing PD-1L [36]. Moreover, an increase in the number of tumor-promoting M2-macrophages/ monocytes has been found to occur not only locally,…”
Section: Sting Mrna Expression In Peripheral Blood Mononuclear Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…36 PD-L1+ immune cells were in greater abundance surrounding metastatic lymph nodes, consistent with reports that advanced disease has higher levels of PD-L1 expression. 36,37 Ionizing Radiation, the Immune System, and the Abscopal Effect…”
Section: Reviewmentioning
confidence: 99%
“…The co-expression of the PD-1 with its ligand 1 (PD-L1) on Tregs enhances their proliferation and favors the maintenance of self-tolerance. 5 Human leukocyte antigen G, a nonclassical human leukocyte antigen (HLA), known as a tolerogenic molecule, is capable of downregulating the natural killer (NK) cells' cytotoxic activity, the inhibition of T cell migration, the induction of the apoptosis of activated CD8+ T cells, and the prevention of DC maturation. It induces the functional silencing of the immune response, which is indispensable in certain physiological settings, e.g., during pregnancy, but it also allows the tumor cells to escape the host's immune system.…”
Section: Introductionmentioning
confidence: 99%